Outbreak of Ralstonia mannitolilytica Infection in Hemato-Oncology Unit: Case Series and Review of Literature - Chauhan, Priyanka; Gupta, Anshul; Sahu, Chinmoy; Desai, Nihar; Nityanand, Soniya (Indian Journal of Medical and Paediatric Oncology, 2022)
Ralstonia mannitolilytica is a Gram-negative, nonfermentative, soil bacterium that is reported to cause opportunistic infections in immunocompromised patients in nosocomial settings. After extensive review of literature, it was found that this is second outbreak reported from India. This study is a retrospective analysis of the clinical features, outcome, and source identification of R. mannitolilytica infection outbreak in a hemato-oncology unit of a tertiary care center of North India between February 2020 and March 2020. We report an outbreak of R. mannitolilytica bacteremia (with or without septic shock) in five patients admitted in hemato-oncology unit at a tertiary care institute in North India for 1 month period. Four patients were cured after administration of appropriate antibiotics as per sensitivity reports, while one patient died of septicemia due to delayed diagnosis. Environmental cultures revealed multidose saline bottles used for administration of drugs as the source of outbreak. Following implementation of use of single dose diluents and flushing solutions in patients with central venous catheter, no new case was reported. Clinicians and microbiologists should keep high index of suspicion to identify these organisms as timely diagnosis is the only key to improve outcomes.
Keywords: Ralstonia; outbreak; hematology; infections; microbiology